Batsyeba: dari selingkuhan menjadi ibu Suri dan leluhur Kristus - Sonny Zaluchu; Mesiwarati Waruwu; Martina Novalina (UIN Sunan Gunung Djati Bandung, 2021)
This study analyzes cases of adultery in the Bible between David, the King of Israel, and Bathsheba, the wife of one of his officers. The approach taken for analysis is a mixed narrative analysis with psychology and sociology perspectives. However, the theological frame remains the mainframe in the discussion, especially in finding the motive behind Bathsheba's desire to grant all of David's requests. The result is the conclusion that this narrative should not stop after sin and adultery. Without realizing it, both Bathsheba and David turned out to be in a divine setting that it could only read in the ending of the New Testament, where the descendants of David and Bathsheba became an essential element in the lineage of Judah that gave birth to Jesus the Messiah.